GOOD CORPORATE GOVERNANCE FOR SHARIA MICRO FINANCIAL INSTITUTION - Mulato, Tri (I-Economics, 2018)
Abstract The growth of sharia financial institutions in Indonesia has experienced excellent growth, and has contributed to the development of the country. The existence of sharia financial institutions is increasingly in demand and many investors to develop sharia financial institutions. Without exception, sharia micro financial institutions consisting of BPRS and BMT. The account of BMT and BPRS continues to grow and experience growth, requiring governance in line with its character. This paper is qualitative, and uses descriptive qualitative analysis method, by describing the growth of sharia micro financial institution that is BPRS and BMT. Then describes the existing Good Corporate Governance (GCG) with BPRS and BMT. The results of this paper indicate that BPRS experienced good growth. Third Party Funds grew by 19.144% and financing grew by 14.862%, while the number of offices decreased by 0.222%. The BMT experienced 72.418 percent of receivables growth, 52.885 percent financing, and assets and placements grew below 40 percent. The concept of GCG with the five principles of Transparency, Accountability, Responsibility, Professional, and Fairness, fits perfectly with BPRS and BMT. It's just that it has different characters so it needs to be added the principle of partnership / friendship. Keywords: Sharia of Financing Banking (BPRS), Baitul Maal Wattamwil (BMT), and Good Corporate Governance (GCG) Abstrak Pertumbuhan lembaga keuangan syariah di Indonesia mengalami pertumbuhan yang sangat baik, serta telah memberikan kontribusi untuk pembangunan negara. Keberadaan lembaga keuangan syariah semakin banyak diminati dan banyak investor untuk mengembangkan lembaga keuangan syariah. Tana terkecuali lembaga keuangan mikro syariah yang terdiri dari BPRS dan BMT. Jumlah BMT dan BPRS terus bertambah serta mengalami pertumbuhan sehingga membutuhkan tata kelola yang sejalan dengan karakternya. Tulisan ini bersifat kualitatif, dan menggunakan metode analisis deskriftif kualitatif, dengan menguraikan pertumbuhan lembaga keuangan mikro syariah yaitu BPRS dan BMT. Kemudian menguraikan Good Corporate Governance (GCG) yang sudah ada dengan BPRS dan BMT. Hasil dalam tulisan ini menujukkan bahwa BPRS mengalami pertumbuhan yang baik Dana Pihak ketiga tumbuh sebesar 19,144 persen dan pembiayaan tumbuh sebesar 14,862 persen, sedangkan jumlah kantor mengalami penurunan sebesar 0,222 persen. Adapun BMT mengalami pertumbuhan piutang sebesar 72,418 persen, pembiayaan 52,885 persen, dan aset serta penempatan tumbuh dibawah 40 persen. Konsep GCG dengan lima prinsip Transparansi, Akuntabilitas, Tanggungjawab, Profesional, dan Kewajaran, sangat cocok dengan BPRS dan BMT. Hanya saja memiliki karakter yang berbeda sehingga perlu ditambah prinsip kemitraan/silaturahim dalam kegiatannya. Kata Kunci : Bank Pembiayaan Rakyat Syariah (BPRS), Baitul Maal Wattamwil (BMT), dan Good Corporate Governance (GCG)